2018
DOI: 10.3390/ijms19061589
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics for Inflammatory-Related Diseases Based on Plasmon-Activated Water: A Review

Abstract: It is recognized that the properties of liquid water can be markedly different from those of bulk one when it is in contact with hydrophobic surfaces or is confined in nano-environments. Because our knowledge regarding water structure on the molecular level of dynamic equilibrium within a picosecond time scale is far from completeness all of water’s conventionally known properties are based on inert “bulk liquid water” with a tetrahedral hydrogen-bonded structure. Actually, the strength of water’s hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…muciniphila can ameliorate IBD severity. In other words, PAW may have antitumor potential [ 12 , 49 ], and A . muciniphila may help repair intestinal barriers [ 41 , 51 , 52 , 53 ] by promoting the secretion of colonic mucins [ 54 ] and increasing the thickness of the mucus layer [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…muciniphila can ameliorate IBD severity. In other words, PAW may have antitumor potential [ 12 , 49 ], and A . muciniphila may help repair intestinal barriers [ 41 , 51 , 52 , 53 ] by promoting the secretion of colonic mucins [ 54 ] and increasing the thickness of the mucus layer [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmon-activated water (PAW), prepared by using Au nanoparticles (AuNP)-adsorbed ceramics under resonant illumination with a green light-emitting diode, has various molecular properties (e.g., antioxidant and anti-inflammatory) and functions [ 10 , 11 ]. Daily consumption of PAW, which has potential anti-tumor metastatic properties [ 11 ], can mitigate various inflammatory-related diseases [ 12 , 13 ]. However, as far as we know, few studies have focused on the anti-inflammatory properties of PAW on IBD treatment by changing the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Hot electron transfer can promote numerous chemical reactions [ 36 ], including dissociation of hydrogen [ 37 ], activation of oxygen [ 38 ], as well as electrocatalytic hydrogen evolution [ 39 ]. Our group proposed an innovative method to create PAW, which is prepared by treating ROW with resonantly excited AuNPs [ 1 , 40 , 41 ]. Recently, we have demonstrated that PAW is innovatively applicable in various fields [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group proposed an innovative method to create PAW, which is prepared by treating ROW with resonantly excited AuNPs [ 1 , 40 , 41 ]. Recently, we have demonstrated that PAW is innovatively applicable in various fields [ 40 ]. PAW, with its unique properties of enhancing solute diffusion, as well as its exhibited anti-inflammatory properties, considerably shortens the time required to remove uremic contaminants during hemodialysis therapy [ 2 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group proposed an innovative method to create PAW, which is prepared by treating ROW with resonantly excited AuNPs 10,37,38 . Recently, we have demonstrated that PAW is innovatively applicable in various elds 39 . PAW with its unique properties of enhancing solute diffusion as well as exhibiting anti-in ammatory properties considerably shortens the time required to remove uremic contaminants during hemodialysis therapy 11,40 .…”
Section: Discussionmentioning
confidence: 99%